UJI DAYA HAMBAT CACING TANAH (Lumbricus rubellus) TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi SECARA IN VITRO - Suryanata Kesuma; Lamri Lamri; Marezha Aulia Putri Sugiarsono (Husada Mahakam, 2022)
One of the pathogenic microbes that often infect humans is Salmonella typhi which causes typhoid fever. Antibiotics are the main choice in treating typhoid fever. Herbal ingredients are very safe for humans because they contain active compounds as effective antiseptics. In the modern world today, the active compound lumbricin in earthworms (Lumbricus rubellus) is used as a medicinal ingredient. The purpose of the study was to determine the diameter of the inhibition zone and to determine the effectiveness of the inhibition of earthworm powder (Lumbricus rubellus) with concentrations of 25%, 50%, and 100% against the growth of Salmonella typhi bacteria. This type of research is a laboratory experiment. Earthworm (Lumbricus rubellus) is processed into powder by roasting technique, then made in the form of a medicinal disc. Earthworm powder was tested for sensitivity by disc diffusion method in concentrations of 25%, 50%, and 100% against the growth of Salmonella typhi, which was cultured in Muller Hinton Agar media with a clear zone formed for 24 hours. The study results were carried out with seven repetitions at a concentration of 25% no antibacterial power and antibacterial effectiveness. However, at concentrations of 50% and 100%, the average diameter of the inhibition zones was 0.21 mm and 0.92 mm, and the antibacterial efficacy was 0.7% and 3.4%, respectively. This study concludes is that at a minimum concentration of 50%, antibacterial power and effectiveness were obtained.